Experimental Investigation on the Interfacial Debonding between FRP Sheet and Concrete under Medium Strain Rate - Zihua Zhang; Yunyi Xiao; Ping Zhuge; Xiaocun Zhang (International Journal of Polymer Science)
Fiber-reinforced polymer (FRP) composites have been widely used to strengthen the existing reinforced concrete (RC) structures to against static and dynamic loads. During the past decades, the interfacial bond behavior between FRP and the concrete substrate under static load has been systematically investigated by experimental and numerical approaches. In contrast, the interfacial bond performance under dynamic loads, e.g., impact and explosive loading, is still far away from well known, especially taking the strain rate effect into account. In this contribution, the single-lap shear test is conducted to sixty specimens at the medium strain rate between 1.0E−4/s and 5.0E−3/s. The effects of various system parameters, including the strain rate, concrete strength, type of FRP and adhesive, on the interfacial fracture energy, peak shear stress, FRP strain distribution, interfacial shear stress, and effective bond length, are thoroughly investigated. It has been revealed that the strain rate and concrete strength can significantly affect the interfacial fracture energy and peak shear stress. The specimen with CFRP sheet possesses higher interfacial shear stress but lower fracture energy than that with BFRP sheet. The adhesive with lower elastic modulus is helpful to improve interfacial energy dissipation under dynamic load. The effective bond length decreases with concrete strength and strain rate, mainly between 75 mm and 90 mm, which is significantly shorter than that under static load. Inspired from the Kulkarni and Shah model, a new model is proposed to evaluate the interfacial fracture energy and peak shear stress with respect to the strain rate, and the estimated values agree well with the experiments.